2004
DOI: 10.1109/tits.2004.838180
|View full text |Cite
|
Sign up to set email alerts
|

Urban Traffic Control Structure Based on Hybrid Petri Nets

Abstract: An urban network of signalized intersections can be suitably modeled as a hybrid system, in which the vehicle flow behavior is described by means of a time-driven model and the traffic light dynamics are represented by a discrete event model. In this paper, a model of such a network via hybrid Petri nets is used to state and solve the problem of coordinating several traffic lights with the aim of improving the performance of some classes of special vehicles, i.e., public and emergency vehicles. The proposed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(55 citation statements)
references
References 26 publications
0
51
0
4
Order By: Relevance
“…According to some existing works, the modelling of the systems by using Petri nets formalisms can be considered from either a discrete and/or a continuous point of view. Continuous Petri nets for the macroscopic and microscopic traffic flow control are used in [15]- [34], while hybrid Petri nets are used in [11] to provide a valuable model of urban networks of signalized intersections. Recently, batch Petri nets with controllable batch speed are used [10] to study a portion of the A12 highway in The Netherlands.…”
Section: A Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…According to some existing works, the modelling of the systems by using Petri nets formalisms can be considered from either a discrete and/or a continuous point of view. Continuous Petri nets for the macroscopic and microscopic traffic flow control are used in [15]- [34], while hybrid Petri nets are used in [11] to provide a valuable model of urban networks of signalized intersections. Recently, batch Petri nets with controllable batch speed are used [10] to study a portion of the A12 highway in The Netherlands.…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…These are a few works that demonstrate the high potential of Petri nets as a tool for modelling and performance analysis of urban transportation systems, but also on the other hand, it is shown that the application of Petri nets is still in its early stage and particularly limited to intersection traffic control [11]- [14]- [15]- [25]- [35]- [34] and to some studies dealing with the modelling of urban transportation systems for planning purposes [28]- [29]- [33]. In addition, according to our knowledge, unlike traditional urban transportation systems, no work has been undertaken on PBS systems modelling and performances analysis by using Petri net models.…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…Besides widely deployed UTC systems such as the Sydney Coordinated Adaptive Traffic System (SCATS) [8], [9] and the Split Cycle Offset Optimization Technique (SCOOT) [10], numerous approaches to UTC have been proposed as computational problem-solving methodologies have evolved. Such approaches mainly use Dynamic Programming (DP) [11], [12], [13], [14], graph theory [15], Petri Nets [16] and game theory [17]. Others simply use heuristic models and rule based/logical programming approaches [18], [19].…”
Section: Billion Inmentioning
confidence: 99%
“…[16] uses hybrid Petri Nets to model the traffic network and a supervisor to coordinate all signalized junctions. Several DP approaches to UTC optimiza tion also exist [26], [11], [12], [14], [13], [27].…”
Section: Related Workmentioning
confidence: 99%
“…In [5], Petri nets are used to model the control of signalized intersections, and the good properties of the system are evaluated by means of invariant analysis and simulation. In [6], timed Petri nets are applied with the aim of minimizing congestion situations via a traffic-responsive signaling control procedure.…”
Section: Introductionmentioning
confidence: 99%